Severity of Inpatient Hospitalizations Among Undocumented Immigrants and Medi-Cal Patients in a Los Angeles, California, Hospital: 2019 - Ro, Annie; Yang, Helen W.; Du, Senxi; Hanlon, Courtney L.; Young, Andrew Shane (American journal of public health (1971), 2021)
Objectives. To compare the severity of inpatient hospitalizations between undocumented immigrants and Medi-Cal patients in a large safety-net hospital in Los Angeles, California. Methods. We conducted a retrospective analysis of all 2019 inpatient stays at a Los Angeles hospital (n = 22 480), including patients of all races/ethnicities. We examined 3 measures by using insurance status to approximate immigration status: illness severity, length of hospital stay, and repeat hospitalizations. We calculated group differences between undocumented and Medi-Cal patients by using inverse probability weighted regression adjustment separately for patients aged 18 to 64 years and those aged 65 years and older. Results. Younger undocumented patients had less severe illness and shorter lengths of stay than their Medi-Cal counterparts. Older undocumented immigrants also had less severe illness, but had similar lengths of stay and were more likely to have repeated hospitalizations. Conclusions. While existing work suggests that undocumented immigrants could have more severe health care needs on account of their poorer access to medical care, we did not see clear health disadvantages among hospitalized undocumented immigrants, especially younger patients. There were fewer differences between undocumented and Medi-Cal patients who were older. (Am J Public Health. 2021;111(11):2019–2026. https://doi.org/10.2105/AJPH.2021.306485 )